Molecular characterization of Xanthomonas axonopodis pv. vignaeradiatae, causing bacterial leaf spot of green gram - Kumar, Jitendra; Doshi, Anila (Indian Journal of Plant Protection, 2020)
Xanthomonas axonopodis pv. vignaeradiatae causes bacterial leaf spot of green gram, an industrially important legume. Ten isolates of X. axonopodis pv. vignaeradiatae, obtained from green gram fields of Udaipur district, Rajasthan were identified at the pathovar level using virulence trials on the susceptible green gram genotype (SML 668), which confirmed their phytopathogenic specialization on green gram. Polymerase chain reaction (PCR)-based techniques such as, random amplified polymorphic DNA (RAPD)–PCR was successfully employed to elucidate the pathogen population structure and intra pathovar relationship among a set of ten X. axonopodis pv. vignaeradiatae isolates. There was a significant variation in their pathogenicity and genetic structure. The pathogenicity data were found to be in line with the molecular data to some extent. RAPD markers revealed a high level of genetic diversity across the isolates employed in comparison. There was no correlation between DNA amplification product patterns and geographic sites of isolation, suggesting that this bacterium has spread largely through exchange of infected plant germplasm. This is the first report on the molecular characterization of X. axonopodis pv. vignaeradiatae isolates from Rajasthan, India.